How to develop new systemic treatments in ultra-rare cancers with high unmet needs?: The case of alveolar soft-part sarcoma - Stacchiotti, Silvia; Bouche, Gauthier; Herold, Ralf; Pantziarka, Pan; Schuster, Kathrin; Wilson, Roger; Pignatti, Francesco; Kasper, Bernd (European journal of cancer, 2024)
Developing new drugs or generating evidence for existing drugs in new indications for ultra-rare cancers is complex and carries a high-risk of failure. This gets even harder in ultra-rare tumours, which have an annual incidence of 1 per 1,000,000 population or less. Here, we illustrate the problem of adequate evidence generation in ultra-rare tumours, using Alveolar Soft-Part Sarcomas (ASPS) - an ultra-rare sarcoma newly diagnosed in approximately 60 persons a year in the European Union - as an exemplar case showing challenges in development despite being potentially relevant for classes of agents. We discuss some possible approaches for addressing such challenges, especially focussing on constructive collaboration between academic groups, patients and advocates, drug manufacturers, and regulators to optimise drug development in ultra-rare cancers. This article, written by various European stakeholders, proposes a way forward to ultimately get better options for patients with ultra-rare cancers.